Arterial stiffness before and after moderate intensity exercise in athletes and controls: a cross-sectional observational study. Issue 2 (20th January 2011) - Dulai, R; Ahmed, M; Morrissey, D; Twycross-Lewis, R; Greenwald, S
Abstract : Background: Arterial stiffness is an independent predictor for cardiovascular disease and mortality. There has been no previous research comparing the acute effects of exercise on arterial stiffness in resistance and endurance athletes. This information would help to reveal how arterial function responds to exercise training. Objectives: To measure and compare arterial stiffness and hemodynamic variables in resistance athletes, endurance athletes and controls, before and after moderate intensity exercise. Methods: Central and peripheral pulse wave velocity (PWV) was measured using Doppler ultrasound and calculated by the 'foot to foot' method before and after exercise. PWV was initially measured at rest for a 1 min period. Thereafter subjects cycled for 30 min at moderate intensity (60% of maximum heart rate, based on age). PWV was measured at postexercise intervals of 3, 15 and 30 min. Blood pressure and heart rate measurement preceded all PWV measurements. Results: Controls were significantly younger than both athletic groups (p<0.05). Groups did not significantly differ in resting PWV. There was no change in central/peripheral PWV after exercise in the resistance and control groups. Central PWV significantly increased post exercise in endurance athletes (mean (sd) resting PWV: 8.0 (2.0) m/s; 3 min postexercise: 10.5 (4.0) m/s; p=0.027, 95% CIs: 0.30 to 4.42) and recovered to resting values by 15 min. Systolic blood pressure increased significantly (p<0.05) in the endurance group from 136 (16) g at rest to 151 (13) 3 min after exercise. Conclusions: PWV in the endurance group significantly increased after exercise, possibly due to the concomitant rise in blood pressure. However, PWV did not change in response to exercise in the resistance or control groups. Lack of significant differences between the groups may be explained by problems with ultrasound measurement and a small sample size in the resistance group.